Evidence of survival bias in the association between APOE-Є4 and age at ischemic stroke onset - von Berg, Joanna; McArdle, Patrick F.; Häppölä, Paavo; Haessler, Jeffrey; Kooperberg, Charles; Lemmens, Robin; Pezzini, Alessandro; Thijs, Vincent; Pulit, Sara L.; Kittner, Steven J.; Mitchell, Braxton D.; de Ridder, Jeroen; et al. (Frontiers in Genetics, 2024)
Introduction Large genome-wide association studies (GWASs) using case–control study designs have now identified tens of loci associated with ischemic stroke (IS). As a complement to these studies, we performed GWAS in a case-only design to identify loci influencing the age at onset (AAO) of ischemic stroke. Methods Analyses were conducted in a discovery cohort of 10,857 ischemic stroke cases using a linear regression framework. We meta-analyzed all SNPs with p-value <1 x 10−5 in a sexcombined or sex-stratified analysis using summary data from two additional replication cohorts. Results In the women-only meta-analysis, we detected significant evidence for the association of AAO with rs429358, an exonic variant in apolipoprotein E (APOE) that encodes for the APOE-Є4 allele. Each copy of the rs429358:T>C allele was associated with a 1.29-year earlier stroke AAO (meta p-value = 2.48 x 10−11). This APOE variant has previously been associated with increased mortality and ischemic stroke AAO. We hypothesized that the association with AAO may reflect a survival bias attributable to an age-related decrease in mortality among APOE-Є4 carriers and have no association to stroke AAO per se. A simulation study showed that a variant associated with overall mortality might indeed be detected with an AAO analysis. A variant with a 2-fold increase in mortality risk would lead to an observed effect of AAO that is comparable to what we found. Discussion In conclusion, we detected a robust association of the APOE locus with stroke AAO and provided simulations to suggest that this association may be unrelated to ischemic stroke per se but related to a general survival bias.